Analisis Sifat Fisis dan Mekanik Biodegradable Foam Berbahan Dasar Selulosa Jerami Padi dan Polivinyl Alcohol - Haiqal, Helmi; Muldarisnur, Mulda (Jurnal Fisika Unand, 2023)
Research has been carried out on analyzing the physical and mechanical properties of biodegradable foam made from rice straw cellulose with a polyvinyl alcohol binding matrix. This study aims to produce a substitute for styrofoam, which is considered not environmentally friendly and harmful to health. The composition of straw fiber and polyvinyl alcohol was varied by the mass ratio of the mixture of rice straw fiber and PVA (%) 40:20%, 30:30%, 20:40%, 50:10%, with the size of the fiber passing through the 80 mesh sieve. The results of the characterization using FT-IR showed that the highest content of functional groups was carbon (C), which corresponds to the content of conventional biofoam, which consists of the elements carbon (C) and hydrogen (H). The highest biofoam tensile strength value is in the comparison fraction (20:40%) of 18.11 MPa. The highest percentage of biofoam water absorption was obtained in the fraction ratio (50:10%) of 0.8928% in the treated sample and 1.1928% in the untreated sample. The percentage of biofoam water content closest to conventional biofoam water content is obtained at a fraction ratio (40:20%) of 0.78%. The highest degradation rate was obtained in samples with a comparative fraction (50:10%) of 0.04237%/day in treated and 0.06403%/day in untreated samples. The results of this study stated that the resulting biofoam did not contain harmful substances. After identifying the functional groups using the FT-IR test, the tensile strength of biofoam still did not meet the SNI 7188.7: 2016 bioplastic standard.